FAKTOR-FAKTOR PENYEBAB TERJADINYA PERKAWINAN USIA MUDA DIKALANGAN REMAJA DI DESA TEMBUNG KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - SITI YULI ASTUTY (Welfare StatE, 2013)
ii This thesis is entitled "Factors Causing Occurrence Amongst Young Age Teens Marriage in the Village District Tembung Percut Sei Tuan Deli Serdang regency". This study aimed to describe the factors that lead to early marriage among teenagers and to describe the forms of family upbringing young couples. Results from this study are expected to be material for parents to enter, so do not rush to immediately marry children in adolescence. Because teens have not been able to face and resolve domestic problems as well. The teens still need to stock a lot of good stock of physical maturity, mental and social economics, general science, religion, life experiences in married life. The study was conducted in the village of Sei Tuan Tembung Percut District Deli Serdang regency. This research is descriptive, where the informants in this study were adolescents who had been married at a young age as many as 3 people and parents of informants. Data collection techniques to the study of literature, field studies, in-depth interviews and observation. The data obtained in the field and then analyzed and compiled in a draft of questions and answers between researchers described qualitatively. The results show conclusively that the environmental factors and parental considerable influence on the formation of self-concept in children, because the child saw her mother who also did a lot of early marriage. Factors parents of low economic level caused many parents marry off their children at a young age. Keywords: factors of early marriage, teenage.